Berwakaf sebagai New Life Style : Strategi Komunikasi BWI pada Akun Instagram di Kalangan Milenial : Berwakaf sebagai New Life Style : Strategi Komunikasi BWI pada Akun Instagram di Kalangan Milenial - Qurrota A'yun, Qurrota A'yun; Achmad Muhibbin Zuhri; Rahma Hanim Azzahra (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
Waqf is an important investment for the future, the right waqf can also support an increase in welfare for people in need. With the existence of productive waqf, at least it has helped the economy, education and even social activities in the community. Nowadays, many of the millennial generation are using the internet as a new lifestyle, thus BWI also uses the internet as a communication support to form a waqf movement so that it can be understood in this lifestyle in the modern era. The purpose of this study is to find out how the communication strategy of the Indonesian Waqf Agency (BWI) in promoting waqf as a new lifestyle among Millennials through its official Instagram account. This research focuses on how BWI can use technology in the modern era such as Instagram, to understand the community and increase concern and solidarity in the quality of life in the hereafter. The results of the study show that BWI's communication strategy based on information technology has increased the awareness, understanding and participation of the Millennial community as part of the Islamic lifestyle. What is evidenced by the number of followers/followers on the account is also some evidence of posts that are attractively packaged Keywords : Waqf, New Lifestyle, Social Media